2016
DOI: 10.1111/clr.12795
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic outcome of immediately restored single implants placed in extraction sockets and healed sites of the anterior maxilla: a retrospective study on 103 patients with 3 years of follow‐up

Abstract: Both immediate and conventional single-implant treatment in the anterior maxilla can yield satisfactory aesthetic outcomes, when performed by experienced clinicians in well-selected cases. Further studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 51 publications
(122 reference statements)
3
88
0
4
Order By: Relevance
“…Several authors have suggested that primary stability may be a useful predictor for osseointegration [29][30][31][32][33][34][35] and that a high primary stability makes immediate loading more predictable [19,20,26,27] [32]. In fact, in that study, no implant with ISQ > 60 failed, while 19% of implants with ISQ < 60 failed [32].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several authors have suggested that primary stability may be a useful predictor for osseointegration [29][30][31][32][33][34][35] and that a high primary stability makes immediate loading more predictable [19,20,26,27] [32]. In fact, in that study, no implant with ISQ > 60 failed, while 19% of implants with ISQ < 60 failed [32].…”
Section: Discussionmentioning
confidence: 90%
“…In modern implantology, with the introduction of surgical and prosthetic protocols such as the immediate placement of implants in fresh postextraction sockets [19,[24][25][26] and immediate functional loading [19,20,27], it is very important to quantify implant stability at various timeframes, in order to have a long-term prognosis for the implants placed [10,[14][15][16][17][18]. Therefore, the employment of simple, clinically applicable noninvasive tests to assess implant stability and osseointegration can be considered valuable [12][13][14][15][16][17][18]23].…”
Section: Introductionmentioning
confidence: 99%
“…The tapered design with double lead threads, in fact, allows the surgeon to obtain an excellent primary implant stability even in difficult clinical conditions [12], such as in the case of postextraction sockets [20]. At the same time, the dual acid etched surface of these implants has the potential to accelerate bone healing, as demonstrated by a recent histologic/histomorphometric human study [13].…”
Section: Discussionmentioning
confidence: 99%
“…All fixtures used in the present study (TixOs ® , Leader, Milan, Italy) were fabricated as previously described [26,27,28,29,30,31]. In brief, titanium alloy (Ti 6 Al 4 V) powders with a particle size of 25–45 μm were used as basic material in an argon atmosphere, and sintered together, layer by layer, through a DMLS process.…”
Section: Methodsmentioning
confidence: 99%
“…Several reviews [24], research [25,26,27,28], and clinical studies [29,30,31] have demonstrated the potential advantages and applications of the DMLS technique for the fabrication of dental implants, even with custom shapes [32,33]. …”
Section: Introductionmentioning
confidence: 99%